An evidence mapping of systematic reviews and meta-analysis on traditional Chinese medicine for ulcerative colitis - Yu-Xin Sun; Xiao Wang; Xing Liao; Jing Guo; Wen-Bin Hou; Xin Wang; Jian-Ping Liu; Zhao-Lan Liu (BMC, 2021)
Abstract Background Traditional Chinese Medicine (TCM) has been a proposed treatment option for ulcerative colitis (UC), however it has been difficult to understand the breadth and depth of evidence as various Chinese medicine therapies may produce effects differently. The aim of this evidence mapping is to visually understand the available evidence in the use of TCM in the treatment of UC, and to identify gaps in evidence to inform priorities of future research. Methods A systematic electronic literature search of six databases were performed to identify systematic reviews (SRs) on different Chinese medicine therapies in the treatment in UC. Methodological quality of the included SRs was assessed using AMSTAR 2. Results The mapping was based on 73 SRs, which included nine interventions that met eligibility criteria. The quality of the included SRs was very low. The diseases stages of patients with UC varied greatly, from active to remission, to non-acute outbreak, to not reported. The results mostly favored the method of intervention. Oral administration combined with enema was the most widely used route of administration in secondary research. Conclusion Based on the current evidence, the treatment of UC with TCM can only be recommended cautiously. A majority of included SRs did not report the location of the disease, the disease classification, and the route of administration of the intervention. Further research is needed on the effectiveness of Chinese medicine alone in the treatment of UC. The effectiveness of combined Chinese and conventional medicine combined with different routes of administration cannot be confirmed. Attention should be paid to the methodological quality of the systematic review. Unifies the outcome indicators used in the evaluation of effectiveness.